Deciphering Inflammasome Mechanisms in Periodontal Diseases: A Review - Himani Sharma; Anamika Sharma; Umang Tripathi (Archives of Medicine and Health Sciences)
Inflammasomes are complex multimeric protein molecules that play a central role in orchestrating the inflammatory response within periodontal tissues. These structures, primarily located in immune cells like macrophages and dendritic cells, become activated when exposed to microbial pathogens which are commonly found in dental plaque. Inflammasomes, crucial regulators of inflammation, play a significant role in periodontal diseases. Activation of inflammasomes, particularly NOD-like receptor family, pyrin domain-containing 3, triggers the release of pro-inflammatory cytokines, exacerbating tissue destruction in the periodontium. The aim of this review is to comprehensively explore the role of inflammasomes in periodontology, elucidating their involvement in periodontal diseases, discussing the mechanisms of inflammasome activation, and evaluating their potential as therapeutic targets. A comprehensive search was conducted across three databases, namely PubMed, Medline, and Google Scholar, focusing on the role of inflammasomes in periodontology: Various search terms including inflammasome, periodontitis, inflammation, oral health, and related keywords were employed to identify relevant studies.